The group action on a projective plane over finite field of order sixteen - AL-Seraji, Najm A. M.; AL-Ogali, Riyam A. B. (Iraqi Journal of Science, 2021)
The goal of this paper is to construct an arcs of size five and six with stabilizer groups of type alternating group of degree five and degree six . Also construct an arc of degree five and size with its stabilizer group, and then study the effect of and on the points of projective plane. Also, find a pentastigm which has the points on a line. Partitions on projective plane of order sixteen into subplanes and arcs have been described.